2022
DOI: 10.3390/app12168151
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Oxygen- and Carbon-Related Defects in Electron Irradiated Cz–Si Doped with Isovalent Impurities

Abstract: Crystalline silicon (Si) is the key material of the semiconductor industry, with significant applications for electronic and microelectronic devices. The properties of Si are affected by impurities and defects introduced into the material either during growth and/or material processing. Oxygen (O) and carbon (C) are the main impurities incorporated into the crystal lattice during growth via the Czochralski method. Both impurities are electrically neutral, however, implantations/irradiations of Si lead to the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 156 publications
0
1
0
Order By: Relevance
“…Aside from oxygen, carbon is an important impurity in Si unintentionally added during material growth [1,9,15,16]. In previous studies, the interactions of C with selfinterstitials and various impurities have been reported to mainly be with O and other C atoms, leading to families of (C-O)-related (for instance, C i O i , C i O i (Si i ) n ) [9,[16][17][18][19][20] and C-related defects (for instance, C i C s , C i C s (Si i ) n ) [9,16,[21][22][23][24]. Notably, carbon affects oxygen precipitation [25,26] in Si.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from oxygen, carbon is an important impurity in Si unintentionally added during material growth [1,9,15,16]. In previous studies, the interactions of C with selfinterstitials and various impurities have been reported to mainly be with O and other C atoms, leading to families of (C-O)-related (for instance, C i O i , C i O i (Si i ) n ) [9,[16][17][18][19][20] and C-related defects (for instance, C i C s , C i C s (Si i ) n ) [9,16,[21][22][23][24]. Notably, carbon affects oxygen precipitation [25,26] in Si.…”
Section: Introductionmentioning
confidence: 99%